2023
DOI: 10.1002/alz.13036
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in associations between APOE ε2 and longitudinal cognitive decline

Abstract: INTRODUCTIONWe examined whether sex modifies the association between APOE ε2 and cognitive decline in two independent samples.METHODSWe used observational data from cognitively unimpaired non‐Hispanic White (NHW) and non‐Hispanic Black (NHB) adults. Linear mixed models examined interactive associations of APOE genotype (ε2 or ε4 carrier vs. ε3/ε3) and sex on cognitive decline in NHW and NHB participants separately.RESULTSIn both Sample 1 (N = 9766) and Sample 2 (N = 915), sex modified the association between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
(134 reference statements)
3
2
0
Order By: Relevance
“…14 Additionally, a recent study found that the APOE ε2 association with cognitive decline in cognitively normal White men was stronger than in White women. 56 In the present analysis, which included some of the same cohorts, we saw similar evidence of a stronger association between APOE ε2 and longitudinal decline in cognitively normal White men compared with cognitively normal White women, but the APOE ε2 × sex interaction did not…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…14 Additionally, a recent study found that the APOE ε2 association with cognitive decline in cognitively normal White men was stronger than in White women. 56 In the present analysis, which included some of the same cohorts, we saw similar evidence of a stronger association between APOE ε2 and longitudinal decline in cognitively normal White men compared with cognitively normal White women, but the APOE ε2 × sex interaction did not…”
Section: Discussionsupporting
confidence: 69%
“… 14 Additionally, a recent study found that the APOE ε2 association with cognitive decline in cognitively normal White men was stronger than in White women. 56 In the present analysis, which included some of the same cohorts, we saw similar evidence of a stronger association between APOE ε2 and longitudinal decline in cognitively normal White men compared with cognitively normal White women, but the APOE ε2 × sex interaction did not reach statistical significance ( Table 3 ). Continued reporting by sex and race will allow for larger studies to confirm whether the intersectional effects and the previous mixed findings in APOE ε2 carriers persist.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Female APOE3/4 heterozygotes have an odds ratio of 4 (compared with 1 in men) of developing AD, and the risk of AD in homozygous APOE 4/4 is also higher in females compared to males [ 51 ]. APOE2 is neuroprotective, but only in women, and may be mediated by a differential lipid expression and biomarkers [ 52 , 53 ]. Lastly, differences in comorbid disease incidence and prevalence may also lead to increased disparity in neurocognitive decline based on sex.…”
Section: Sexual Dimorphism and The Brainmentioning
confidence: 99%
“…Among APOE e4 carriers with moderate to severe AD, disinhibition has been shown to be more common and more severe in women compared to men [ 110 ]. Sex also affected the association between cognitive decline and the APOE e2 allele in non-Hispanic White participants in a recent study, with men displaying slower decline compared to women [ 111 ]. APOE e4 homozygosity among participants with MCI was also related to a greater NPS burden in women compared to men [ 112 ].…”
Section: Future Perspectivesmentioning
confidence: 99%